Effectivity of Bromocriptine Administration Towards Prolactin Positive Breast Cancer Receiving Anthracycline-Based Chemotherapy: A Literature Review - Muhammad Yadi Permana; Sarwanti Sarwanti; Siti Fauziah (Acta Medica Indonesiana)
Breast cancer is among the deadliest gynecology cancers in the world. However, the management of advanced-stage breast cancer is often harder as a result of chemoresistance. This review aimed to discover the effect of bromocriptine on prolactin-positive breast cancer patients who received anthracycline-based chemotherapy. It is known that anthracycline works by inhibiting topoisomerase IIα (TOP2A), forming free radicals, binding DNA, and altering cell homeostasis, hence stopping the cell cycle and inducing cell death. However, reduction of TOP2A expression and increased glutathione s-transferase (GST) and ATP-binding cassette (ATP) membrane activity increase anthracycline efflux from the cell membrane, hence reducing its effectivity. Prolactin is one of the most common chemoresistance agents whose complex with its receptor will induce JAK/STAT pathway to increase GST. The regulation of Bcl-2 and ERK was also determined by prolactin. Bromocriptine is an agonist of the D2 dopamine receptor that inhibits adenyl cyclase and a D1 dopamine weak antagonist. Bromocriptine could reduce prolactin serum and receptors in various cases. Some studies have found that bromocriptine could improve the effectiveness of chemotherapy regimens, including cancer-related hyperprolactinemia, breast cancer that underwent cisplatin, and taxanes. Therefore, bromocriptine offers potential as it could improve outcomes and reduce resistance in prolactin-positive breast cancer patients who are administered anthracycline-based neoadjuvant chemotherapy.